TECHNOLOGY FOR ASSESSING THE EDUCATIONAL RESULTS OF FUTURE TEACHERS IN PHYSICAL CULTURE BASED ON A CASE-TASK - Stafeeva A.V. ,; Ivanova S.S. ,; Burkhanova I.Yu. ,; Krasnova M.S. ,; Mokhova M.E. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop a technology for assessing the educational results of future physical education teachers based on a case-task. Methods and structure of the study. The authors describe the logic of building an educational result in the field of methodological training of a future physical education teacher, which is to be assessed using the GPC-3 competence as an example, indicators of its achievement are highlighted. Results and conclusions. An example of building an assessment tool in the form of a case-task for assessing the educational results of future physical education teachers in the field of methodological training is presented. Criteria, indicators and evaluation scale of the evaluation tool are described, which allow to assess the level of achievement of educational results of future physical education teachers and determine their readiness for professional activities.